FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE SPECIALISTS OF AVIATION - Ладогубець, Наталія Віталіївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The author of the article has analysed the specificity of content and organization of the formative stages of the pedagogical experiment on the formation of professional competence of future professionals in the field of aviation. The results of the experiment have been analysed and conclusions have been formulated